Early life socioeconomic determinants of dietary score and pattern trajectories across six waves of the Longitudinal Study of Australian Children. Issue 12 (9th October 2017) - Gasser, Constantine E; Mensah, Fiona K; Kerr, Jessica A; Wake, Melissa
Abstract : Background: Social patterning of dietary-related diseases may partly be explained by population disparities in children's diets. This study aimed to determine which early life socioeconomic factors best predict dietary trajectories across childhood. Methods: For waves 2–6 of the Baby (B) Cohort (ages 2–3 to 10–11 years) and waves 1–6 of the Kindergarten (K) Cohort (ages 4–5 to 14–15 years) of the Longitudinal Study of Australian Children, we constructed trajectories of dietary scores and of empirically derived dietary patterns. Dietary scores, based on the Australian Dietary Guidelines, summed children's consumption frequencies of seven groups of foods or drinks over the last 24 hours. Dietary patterns at each wave were derived using factor analyses of 12–16 food or drink items. Using multinomial logistic regression analyses, we examined associations of baseline single (parental education, remoteness area, parental employment, income, food security and home ownership) and composite (socioeconomic position and neighbourhood disadvantage) factors with adherence to dietary trajectories. Results: All dietary trajectory outcomes across both cohorts showed profound gradients by composite socioeconomic position but not by neighbourhood disadvantage. For example, odds for children in the lowest relative to highest socioeconomic position quintile being in the 'never healthy' relative to the 'always healthy' score trajectory were OR=16.40, 95% CI 9.40 to 28.61 (B Cohort). Among the single variables, only parental education consistently predicted dietary trajectories. Conclusion: Child dietary trajectories vary profoundly by family socioeconomic position. If causal, reducing dietary inequities may require researching underlying pathways, tackling socioeconomic inequities and targeting health promoting interventions to less educated families.